Catalytic Oxidation of Carbon Monoxide over Transition Metals Oxides - Malikova, I.H.; Efendi, A.J.; Aykan, N.F.; Farajov, H.M.; Yunisova, F.A. (Herald of Azerbaijan Engineering Academy, 2025)
One of the main solutions to prevent air pollution is the reduction of CO by oxidation to CO2. Although it has been known since the beginning of the 20th century that some oxides show significant activity, recently, due to the increase in the price of noble metals and special advances in oxide synthesis, the catalytic oxidation of carbon monoxide over oxide catalysts has gained interest. In this article, the kinetics and mechanism of CO oxidation in simple and mixed oxides, as well as the structures of the catalysts, are investigated.